System study of an integrated facility with arc-jet and expansion tube for hypervelocity testing with ablating spacecraft models - Chang, EWK; Hermann, T (2024)
Ground testing for the atmospheric entry environment requires precise matching of key flow parameters. However, existing hypersonic facilities can only partially replicate some aspects of this complex environment. Plasma wind tunnels can generate continuous high-enthalpy flow, but challenges arise in achieving aerodynamic similarity. Impulse facilities can match the velocity and total pressure of hypersonic flow, but only for a short test duration. A hybrid facility allows a more comprehensive simulation of atmospheric entry conditions by using the small-scale thermal arc-jet Osney Plasma Generator (OPG) to heat the test model, which is then exposed to the hypervelocity flow generated from the Cold-Driven Expansion Tube (CXT). This paper presents a detailed system design study and discussion regarding the capability of an integrated arc-jet/expansion tube facility